POLITICAL REPRESSION IN UZBEKISTAN DURING THE SOVIET UNION PERIOD (SYNAPSES: INSIGHTS ACROSS THE DISCIPLINES, 2026)
This article examines the impact of the period of repression from 1937 to 1953 in Uzbekistan and throughout the entire USSR. The study analyzes the causes and consequences of repressive policies and their effects on the population, poets, writers, and military specialists. At the same time, the article highlights the social and spiritual consequences of economic development and industrial achievements, as well as their influence on literature and science. The paper emphasizes the importance of preserving the historical memory of the victims of repression and passing on their legacy to future generations. Based on scholarly works and historical evidence, the article provides readers and researchers with comprehensive and accessible information about the period of repression.